Experimental lead poisoning in the baboon. Issue 2 (April 1970) - Hopkins, Anthony
Abstract : Hopkins, A. (1970). Brit. J. industr. Med., 27, 130-140. Experimental lead poisoning in the baboon. Twelve large and three infant baboons were poisoned by the intratracheal injection of lead carbonate in doses ranging from 50 to 135 mg/kg for 39 to 362 days. Eight baboons had one or more epileptic fits. Weakness of the limbs, believed to be of central origin, was seen in three of them. The effect of single and multiple doses of lead on the blood lead is recorded. Anaemia and punctate basophilia were not found. Measurements of nerve conduction velocity, electromyography and histological examination showed no abnormality of the peripheral nerves. The different effects of lead upon different species are discussed.